Maintenance and Exchange of the Aromatic Amino Acid Pool in Escherichia coli - Brown, K. D. (1971)
The pool of phenylalanine, tyrosine, and tryptophan is formed in Escherichia coli K-12 by a general aromatic transport system [Michaelis constant (K(m)) for each amino acid approximately 5 × 10(−7)m] and three further transport systems each specific for a single aromatic amino acid (K(m) for each amino acid approximately 2 × 10(−6)m, reference 3). When the external concentration of a particular aromatic amino acid is saturating for both classes of transport system, the free amino acid pool is supplied with external amino acid by both systems. Blocking the general transport system reduces the pool size by 80 to 90% but does not interfere with the supply of the amino acid to protein synthesis. If, however, the external concentration is too low to saturate specific transport, blocking general transport inhibits the incorporation of external amino acid into protein by about 75%. It is concluded that the amino acids transported by either class of transport system can be used for protein synthesis. Dilution of the external amino acid or deprivation of energy causes efflux of the aromatic pool. These results and rapid exchange observed between pool amino acid and external amino acids indicate that the aromatic pool circulates rapidly between the inside and the outside of the cell. Evidence is presented that this exchange is mediated by the aromatic transport systems. Mutation of aroP (a gene specifying general aromatic transport) inhibits exit and exchange of the small pool generated by specific transport. These findings are discussed and a simple physiological model of aromatic pool formation, and exchange, is proposed.